Value-addition of green mussel (Perna viridis) as a convenience food - Gallego, Diana Ganancial
Mussels were first regarded as pest in oyster farms but now, it is now cultured and is used as food for humans. Mussel is a seafood that has many potential and should be developed to maximize its utilization. Many are a bit afraid to eat mussels but with proper preparation, mussels are edible. Mussels are perishable products and many of these products are thrown away. In this experiment, mussel was value-added and developed into a food that is convenient to eat. A snack that can be a cheap alternative source of protein and of other beneficial nutrients such as Omega-3, vitamins, zinc, iron, folate and many others. The total coliform count of the raw mussel was <1600 MPN/100g, this analysis was done to ensure the safety of the product. Mussels were processed into brined dried mussel (BD), flavored dried mussel (FD), coated brined dried mussel (CBD) and coated flavored dried mussel (CFD). A proximate analysis was conducted to know some of the nutritional facts of the final product. The coated dried mussel product has a moisture content of 6.32%, ash content is 5.15%, lipid content is 19.72% and protein is 33.97%. Comparing the proximate results of the coated dried mussel final product to the raw material there is a little difference especially in the protein content and lipid content. Sensory evaluation was carried out to know how the products will be perceived, attributes include general appearance, color, odor, texture, saltiness and sweetness. The coated dried mussel products (brined and flavored) yielded good results and acceptability scores on sensory evaluation.